Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Answer:
Now: 6 yr mean age
in 10 yrs? 16 yr mean age
in 20 yrs? 26 yr mean age
Why? Because regardless of the relationship between each sibling's age, your always adding the 10yrs to each individual, which you are then dividing out to determine the mean age. See proof below:
Including anita, there are 6 people. We'll define each age as an unknown variable. Assume we know nothing about the relationships between their ages
for example sake
anita's age = a
sister 1's age = b
sister 2's age = c
brother 1's age = d
brother 2's age = e
brother 3's age = f
Now:
mean age = (a + b + c + d + e + f)/(6 people) = 6 yrs
in 10 yrs:
mean age = ((a+10) + (b+10) + (c+10) + (d+10) + (e+10) + (f+10))/(6 people)
mean age = (a + b + c + d + e + f + 60)/(6 people)
mean age = (a + b + c + d + e + f)/(6 people) + (60)/(6 people)
mean age = (a + b + c + d + e + f)/(6 people) + 10
Notice the first term is the same expression of the mean age for "Now"
Thus, in 10 yrs:
mean age = 6 + 10 = 16 yrs
The same principle applies for "x" yrs from now, as long as we know what the mean age is "Now"
Now: 6 yr mean age
in 10 yrs? 16 yr mean age
in 20 yrs? 26 yr mean age
Why? Because regardless of the relationship between each sibling's age, your always adding the 10yrs to each individual, which you are then dividing out to determine the mean age. See proof below:
Including anita, there are 6 people. We'll define each age as an unknown variable. Assume we know nothing about the relationships between their ages
for example sake
anita's age = a
sister 1's age = b
sister 2's age = c
brother 1's age = d
brother 2's age = e
brother 3's age = f
Now:
mean age = (a + b + c + d + e + f)/(6 people) = 6 yrs
in 10 yrs:
mean age = ((a+10) + (b+10) + (c+10) + (d+10) + (e+10) + (f+10))/(6 people)
mean age = (a + b + c + d + e + f + 60)/(6 people)
mean age = (a + b + c + d + e + f)/(6 people) + (60)/(6 people)
mean age = (a + b + c + d + e + f)/(6 people) + 10
Notice the first term is the same expression of the mean age for "Now"
Thus, in 10 yrs:
mean age = 6 + 10 = 16 yrs
The same principle applies for "x" yrs from now, as long as we know what the mean age is "Now"
Answer:
10 years from now= 16
20 years = 26
Step-by-step explanation:
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.